The entering results of formation of valeological competence of future teachers in the course of physical education - Borys Maksymchuk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the research consists in development, justification and experimental check of theoretical-methodical bases of formation of valeological competence of the process of physical education of students of pedagogical higher educational institutions. Material & Methods: the level of formation of valeological competence of future teachers in the course of physical education was determined by averaging of estimates by each experimental indicator during the skilled-experimental work. 497 students from 1 till 5 courses, 35 university graduates, working as teachers at schools of Vinnitsa, and 17 teachers of higher education institutions were involved in the forming experiment. Results: the low level of formation of valeological competence of future teachers in the course of physical education in all skilled groups, participating in the pedagogical experiment, creates the objective need of introduction of the developed experimental model of formation valeological competence of future teachers in the course of physical education and complex of reasonable pedagogical conditions. Conclusions: the carried-out entering test showed the similarity of experimental groups in the section of respondents on levels of formation of valeological competence, allows to consider output parameters leveled and to begin implementation of the chosen plan of experiment.